Hubungan Kepuasan Tenaga Kesehatan dalam Penggunaan Sistem Informasi Management Puskesmas (Simpus) di Puskesmas Pakuniran Kecamatan Pakuniran Kabupaten Probolinggo - Zulika Qismiatul Khomariyah; Husnul Khotimah; S. Tauriana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Introduction: Simpus puskesmas management application that simplifies and speeds up services to manage patient information starting from registration, registration, examination (diagnosis) and patient care. The satisfaction of health workers, the response or feedback from users about the use of the system, as well as the assessment of the good and bad sides of the system, is the starting point for system developers to improve the performance of the information system built. Purpose of the study: To determine the relationship between satisfaction of health workers in the use of the puskesmas management information system (Simpus) at the Pakuniran health center.  Method: This study uses a quantitative descriptive approach using Nonprobability sampling technique using Total sampling technique using statistical test Spearman's rho correlation, with data collection instruments using questionnaires. This research was conducted at the Pakuniraan health center in July 2023. Research Results: The results of the spearman rank correlation statistical test obtained results namely (p = 0.000) because the p value <0.05 then Ho was rejected and Ha was accepted Conclusion: that there is a relationship between health worker satisfaction in using the puskesmas management information system (SIMPUS), which means that the better and more appropriate the puskesmas management information system, the higher the level of health worker satisfaction.